Production Functions for Climate Policy Modeling: An Empirical Analysis - Edwin van der Werf (Fondazione Eni Enrico Mattei (FEEM), 2007)
Quantitative models for climate policy modeling differ in the production structure used and in the sizes of the elasticities of substitution. The empirical foundation for both is generally lacking. This paper estimates the parameters of two-level CES production functions with capital, labour and energy as inputs, and is the first to systematically compare all nesting structures. Using industry-level data from 12 OECD countries, we find that the nesting structure where capital and labour are combined first, fits the data best, but for most countries and industries we cannot reject that all three inputs can be put into one single nest. These two nesting structures are used by most climate models. However, while several climate policy models use a Cobb-Douglas function for (part of the) production function, we reject elasticities equal to one, in favour of considerably smaller values. Finally we find evidence for factor-specific technological change. With lower elasticities and with factor-specific technological change, some climate policy models may find a bigger effect of endogenous technological change on mitigating the costs of climate policy.
Keywords: O13; Q32; Q43; Q55; 330; Climate Policy; Input Substitution; Technological Change; Klimaschutz; Wirtschaftsmodell; CES-Produktionsfunktion; Faktorsubstitution; Technischer Fortschritt; Theorie; OECD-Staaten